Review on Challenges of Nutrition Intervention Research at Workplace - Pasaribu, Adi Sutriwanto; Basrowi, Ray Wagiu (Journal of Indonesian Specialized Nutrition, 2024)
Workplace nutrition interventions have become a popular approach to improving employee health and well-being. Nonetheless, such interventions require special attention to ethical aspects to ensure participant well-being, research integrity, and long-term benefits. A literature review was carried out using leading research databases, such as PubMed, Scopus, and Google Scholar. Keywords used include "ethical considerations", "workplace", "nutritional intervention", and "study". Only studies published within the last ten years were included in this review. Each study was analyzed to identify common ethical issues and actions taken to address those issues. The results of the review indicate that key ethical issues in workplace nutrition intervention studies include participant privacy and confidentiality, informed consent, balancing risks and benefits, and potential bias and conflicts of interest. Some studies suggest that employees may feel pressured to participate because of company policies or social expectations. Additionally, several studies revealed deficiencies in data protection and transparency regarding the use of participant data. From the results of the review, it is important to ensure that informed consent is provided clearly and free from pressure. Studies must also ensure the protection of participants' privacy and confidentiality. Furthermore, there is a need to carefully assess the risks and benefits of any nutritional intervention, as well as avoid potential bias in research design and implementation. This review suggests that ethics in studies of workplace nutrition interventions require significant attention. Best practices include strong informed consent, privacy protection, and careful risk evaluation.